النظرية السياسية للفيدرالية وتطبيقاتها الدستورية المقارنة التشريع الفيدرالي، اللامركزية، توزيع السلطات، الحكم المحليّ، والسياسة الخارجية أنموذجا - بن الشيخ, عصام (جامعة الوادي - university of Eloued, 2017)
تعود جذور الفيدرالية إلى مساعي جمع المقاطعات والولايات الأمريكية والسويسرية نهاية القرن الثامن عشر، وانتقالها من الكونفدرالية إلى الدولة الفيدرالية، فقد تأسس الفكر الفيدرالي على أساس توحيد المقاطعات أو بهدف نقل وتحويل السلطات، لكنه يعتمد اليوم طرقا حديثة في توزيع السلطات بين أجزاء الاتحاد، كالولايات أو الأقاليم والمقاطعات، بعد تغيّر وظائف الدولة، واعتماد مبدأ اللامركزية الإدارية، أو مقاربات جديدة للتقسيم الإداري. ومع ذلك، تحتاج الفيدراليات إلى وضع أسس دستورية تحدّد صلاحيات الأقاليم واختصاصات الهيئات الاتحادية المركزية والفيدرالية، خاصة في مجال تمثيل السياسة الخارجية للفيدرالية، ومع تطوّر الديمقراطية، أضحت التجارب الفيدرالية بحاجة إلى قوانين وأسس دستورية واضحة وراسخة، توضّح الصلاحيات التشريعية والتنفيذية والقضائية والاختصاصات المالية للاتحاد، ضمانا للاستقلال والحكم الذاتي داخل الاتحاد. ولا يمكن الجزم بأنّ كلّ الفيدراليات يمكن لها أن تنجح في ضمان استمرار الاتحاد، لأنّ بعض الفيدراليات يكون أقرب إلى الحلّ في حالة الجمود. Federalism was rooted in the efforts to bring together the American and Swiss provinces at the end of the eighteenth century, and their transition from confederation to federalism. Federalism was founded on the basis of the unification of provinces or the transfer of powers .today, it relies on modern methods of distributing power among parts of the Union, such as States, regions and provinces, after the change of State functions, the adoption of administrative decentralization or new approaches to administrative division. However, federations need to establish constitutional foundations that define the powers of the regions and the competencies of federal and federal bodies, especially in the field of foreign policy representation of federalism. As the development of democracy has become, federal experiences need clear and wellestablished constitutional laws and principles, To ensure independence and autonomy within the Union. It can not be said that all federals can succeed in ensuring the continuity of the union, because some federations are closer to a solution in the event of stalemate.
مقال. المجلة الدولية للبحوث القانونية والسياسية . مج1. ع.1. جامعة الوادي
Keywords: الفيدرالية، المركزية، اللامركزية، الاتحاد، التقسيم، المقــاطعات، الاختصاصات، الاستقلالية، التوازن الاتحادي، الحكم الذاتي.; Federalism,Centralization, Decentralization, Union, Division, Provinces, Competencies, Independence, Federal Balance, Autonomy